Challenge in diagnosing tuberculosis on a boy with severely wasted in limited resource area - Marini Siagian; Norman Tanyadji (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2022)
Hunger and malnutrition are still the leading cause of morbidity and mortality among children around the world. Undernutrition increases the risk of tuberculosis (TB) which in turn could worsen undernutrition. Indonesia is currently the second highest newly diagnosed TB in the world after India. TB in children with severely wasted is difficult to diagnose. This is a case report about a 35-month-old boy with severely wasted complicated with hypoglycemia, severe dehydration, and pneumonia. After proper nutritional management without the expected outcome, patient was then worked up for TB resulting negative result of tuberculin skin test (TST). Nevertheless, he was still treated with antituberculosis and had significant improvement, hence continuation to complete 6 mo period of therapy. This case report describes the challenge of diagnosing TB in children with severely wasted in limited resource areas. The reduced immune responses, due to severely wasted, caused subtle clinical signs of TB and decreased sensitivity to tuberculin testing. The unavailability of radiologic examination added further problem in diagnosis. The diagnosis of TB should be considered among children in areas with a high prevalence of TB, presenting with severely wasted refractory to proper nutritional management.